Benefits and Complications of Removing Ureteral Stent Based on the Elapsed Time After Renal Transplantation Surgery - Dadkhah, Farid (Nephrourol Mon, 2016)
BACKGROUND: The most important surgical complications of renal transplantation are stenosis and obstruction of anastomosis of the ureter to the bladder. Although the routine use of the ureteral stents to prevent such complications seems rational, the optimal time to keep the ureteral stent is still controversial. OBJECTIVES: This study presents the benefits and complications of removing the ureteral stent based on the elapsed time after the surgery. PATIENTS AND METHODS: All patients who underwent kidney transplantation between May 2011 and August 2014 in Modarres hospital, Tehran, Iran, were enrolled in the study. The patients were classified into three groups. The ureteral stent was removed 10, 20, and 30 days after the transplantation in these groups. RESULTS: A total of 529 patients underwent kidney transplant surgery in our center. Urologic complications among the three groups consisting of hydronephrosis, urinoma and collection did not have statistically significant differences. CONCLUSIONS: Ureteral stent can be picked up with no increased risk of urologic complications at shorter intervals after the kidney transplantation surgery.